Acrodermatitis continua of Hallopeau with psoriatic arthritis treated with biologics and apremilast - Shohei Igari; Toshiyuki Yamamoto (Wiley, 2023)
Abstract Acrodermatitis continua of Hallopeau (ACH) is a rare variant of acral pustular psoriasis, exclusively involving the distal phalanges and nails of the hands and feet. We herein report a rare case of concurrent ACH and psoriatic arthritis sine psoriasis presenting with dactylitis. The patient was successfully treated with biologics and apremilast.